The Hidden Symbolism of Doro Wet: Cultural, Spiritual, and Historical Significance in Ethiopian Christian Tradition - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
Doro Wet, Ethiopia’s spicy chicken stew, is central to Ethiopian Orthodox Christian culture, yet its spiritual and historical symbolism remains underexplored. This study investigates the dish’s biblical, communal, and regional meanings, drawing on a stratified ethnographic sample of 250 Orthodox Christians (125 male, 125 female; six age groups) across five cities (Addis Ababa, Dire Dawa, Adama, Bahir Dar, Debre Berhan). Data from semi‑structured interviews, participant observation during feasts, and textual analysis of the Kebra Nagast were analysed thematically. Findings confirm that the twelve chicken pieces symbolise the apostles or tribes of Israel (94.8%), eggs represent resurrection (100%), berbere signifies spiritual zeal (91.2%), and injera embodies the Bread of Life (100%). The dish fosters communal bonding through gursha (98.4%) and devotional preparation (91.6%). Eastern Ethiopia shows no substantive variation in core symbolism; minor adaptations (sorghum injera, added spices) are pragmatic. However, significant generational erosion emerged: participants aged 20–30 retain ancestral narratives at half the rate of those over 45 (41% vs. 98%). A sceptical minority (11.6%) predominantly urban, educated youth question literal Solomonic historicity while still practising rituals. Doro Wet is a profound symbol of Ethiopia’s Christian identity, but its meanings are negotiated across generations. The study recommends urgent documentation of oral traditions, intergenerational kitchen workshops, diaspora research, and culturally sensitive culinary tourism to safeguard this intangible heritage. This research enriches understanding of food as a living theological artefact in African Christianity.